Improved Device Performance in Nano Scale Transistor: An Extended Drain SOI MOSFET. (1st January 2016) - Mehrad, Mahsa; Zareiee, Meysam
Abstract : Reducing the size of SOI MOSFET especially in nano regime for applying them in Integrated Circuits is difficult, because of the important problems of Short Channel Effects (SCE). These effects reduce the reliability of the device and it is objective to decrease them. In this paper, the goal is to propose a new structure for SOI MOSFET to improve SCEs. In this case the, the form of drain and channel is changed to obtain more reliable device. In this case, the drain region is extended into the channel improving the performance of the device. The drain has higher doping concentration, which causes better performance. The simulation with two dimensional ATLAS simulator shows that the new structure has better performance than the conventional one in cases of off current, subthreshold slope, threshold voltage, DIBL, maximum electron temperature and drain current which leads to more reliable device.